Attitudes, behaviours and learning resources of amateur rugby union coaches and players towards the ruck event during training and match play - Brooks, Michael (Stellenbosch : Stellenbosch University, 2024)
Thesis ( M Sport Sc)--Stellenbosch University, 2024.